EXERCISE 7 1. Find the sum of each of the following infinite geometric scries: \( \begin{array}{ll}\text { (a) } 2+\frac{2}{3}+\frac{2}{9}+\ldots & \text { (b) }-64+32-16+\ldots \\ \text { (c) } 24-4+\frac{2}{3}-\ldots & \text { (b) Calculate } \sum_{m=0}^{\infty} 3\left(-\frac{1}{2}\right)^{m} \\ \text { (a) Calculate } \sum_{m=1}^{\infty} 8(2)^{-2 m} & \begin{array}{ll}\text { (c) Calculate } \sum_{i=0}^{\infty} \frac{1}{10^{i}} & \text { (c) } 0,5 \dot{4}\end{array} \\ \text { Convert each of the following recurring decimals to a common fraction by } \\ \text { first writing it as a geometric series. } \\ \text { (a) } 0,2 \dot{23} & \text { (b) } 4,2\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
The sum of an infinite geometric series can be found using the formula \( S = \frac{a}{1 - r} \), where \( a \) is the first term and \( r \) is the common ratio. For part (a), \( S = \frac{2}{1 - \frac{1}{3}} = \frac{2}{\frac{2}{3}} = 3 \). For part (b), \( S = \frac{-64}{1 - (-\frac{1}{2})} = \frac{-64}{\frac{3}{2}} = -\frac{128}{3} \). For part (c), \( S = \frac{24}{1 - (-\frac{1}{6})} = \frac{24}{\frac{7}{6}} = \frac{144}{7} \). Now, for the series \( \sum_{m=0}^{\infty} 3\left(-\frac{1}{2}\right)^{m} \), we have \( a = 3 \) and \( r = -\frac{1}{2} \), hence \( S = \frac{3}{1 - (-\frac{1}{2})} = \frac{3}{\frac{3}{2}} = 2 \). Next, for \( \sum_{m=1}^{\infty} 8(2)^{-2 m} \), it's best to rewrite it: \( 8(2)^{-2} + 8(2)^{-4} + \ldots \), where \( a = 2 \) and \( r = \frac{1}{4} \), leading to \( S = \frac{2}{1 - \frac{1}{4}} = \frac{2}{\frac{3}{4}} = \frac{8}{3} \). For \( \sum_{i=0}^{\infty} \frac{1}{10^{i}} \), we have \( a = 1 \) and \( r = \frac{1}{10} \), so \( S = \frac{1}{1 - \frac{1}{10}} = \frac{1}{\frac{9}{10}} = \frac{10}{9} \). To convert the recurring decimal \( 0.2\dot{23} \) into a fraction, denote it as \( x = 0.2223\ldots \). We write it as \( x = 0.2 + 0.0\dot{23} \). The second part can be expressed as a geometric series: \( 0.0\dot{23} = \frac{23}{100} + \frac{23}{10000} + \ldots \). This leads to \( S = \frac{\frac{23}{100}}{1 - \frac{1}{100}} = \frac{\frac{23}{100}}{\frac{99}{100}} = \frac{23}{99} \), and combining yields \( x = 0.2 + \frac{23}{99} = \frac{20}{99} + \frac{23}{99} = \frac{43}{99} \). For \( 4.2 \), write it as \( y = 4 + 0.2\dot{0} \). The recurring part can be treated similarly, resulting in \( 4.2 = 4 + \frac{1}{5} = \frac{21}{5} \). Thus, \( 4.2\ldots = \frac{21}{5} \).